Mesenchymal stem cell-derived exosomes: a possible therapeutic strategy for repairing heart injuries - Zhu, Zeshu; Zhu, Ping; Fan, Xiongwei; Mo, Xiaoyang; Wu, Xiushan (Frontiers in Cell and Developmental Biology, 2023)
Mesenchymal stem cells (MSCs) are one of the most potent therapeutic strategies for repairing cardiac injury. It has been shown in the latest studies that MSCs cannot survive in the heart for a long time. Consequently, the exosomes secreted by MSCs may dominate the repair of heart injury and promote the restoration of cardiac cells, vascular proliferation, immune regulation, etc. Based on the current research, the progress of the acting mechanism, application prospects and challenges of exosomes, including non-coding RNA, in repairing cardiac injuries are summarised in this article.